Perencanaan dan Pembuatan Media Interaktif untuk Simulasi Water Treatment dalam Bentuk Animasi - Darsono, Richard Giovanni; Budhi, Gregorius Satia; Liliana, Liliana (Jurnal Infra, 2016)
Water is the most important element we use on daily basis. However, water often get the less attention from the society. To be thought of, almost all of human activities need to use clean water. Many regions in the Indonesia having no clean water stock. Even without our knowing, water takes important role for humans health.This application will packing purification water process and purification wastewater process with interactive and interesting. Not only explain water purification, this application also completed with the information where wastewater came from around us. For the additional information for the user of this application, this application also provide information about bacteria(s) that have some relantion with the water. This application was made using Adobe Flash CS5.5.Animation in this application will greatly helping user in the process understanding of the material. That matter will affect to increase interest to using application which easy and user friendly.